The nearly forgotten Malay folklore: shall we start with the software? - Abd Rahim, Normaliza (Sakarya University, 2014)
The study focuses on the nearly forgotten Malay folklore in Malaysia. The objectives of the study were to identify and discuss the types of Malay folklore among primary school learners. The samples of the study were 100 male and female students at schools in Selangor. The samples were picked at random from several schools and they were given software to view which consisted of Malay folklore. The subjects were interviewed based on their opinions on the use of the software in disseminating the Malay folklore. The data were analysed by using the discourse analysis method by Brown & Yule (1983). The results revealed that the software has given the awareness of the forgotten Malay folklore and further, it has given the overview of most types of stories in Malay folklore. The subjects seemed to favor most of the stories and state that the technology has given them the opportunity to appreciate the forgotten Malay folklore. The study implicates school students, teachers and researchers in understanding, appreciating, disseminating and identifying the moral values from the Malay folklore.